Terminal uprising - Hines, Jim C (Hines, Jim C. Janitors of the post-apocalypse, 2019)
The Krakau came to Earth in the year 2104. By 2105, humanity had been reduced to shambling, feral monsters. In the Krakau<U+2019>s defense, it was an accident, and a century later, they did come back and try to fix us. Sort of. It<U+2019>s been four months since Marion “Mops” Adamopoulos learned the truth of that accident. Four months since she and her team of hygiene and sanitation specialists stole the EMCS Pufferfish and stopped a bioterrorism attack against the Krakau homeworld. Four months since she set out to find proof of what really happened on Earth all those years ago. Between trying to protect their secrets and fighting the xenocidal Prodryans, who<U+2019>ve been escalating their war against everyone who isn<U+2019>t Prodryan, the Krakau have their tentacles full. Mops<U+2019> mission changes when she learns of a secret Krakau laboratory on Earth. A small group under command of Fleet Admiral Belle-Bonne Sage is working to create a new weapon, one that could bring victory over the Prodryans <U+2026> or drown the galaxy in chaos. To discover the truth, Mops and her rogue cleaning crew will have to do the one thing she fears most: return to Earth, a world overrun by feral apes, wild dogs, savage humans, and worse. (After all, the planet hasn<U+2019>t been cleaned in a century and a half!) What Mops finds in the filthy ruins of humanity could change everything, assuming she survives long enough to share it. Perhaps humanity isn<U+2019>t as dead as the galaxy thought.